Taxonomic diversity of microbial communities in sub-seafloor hydrothermal sediments of the active Santorini-Kolumbo volcanic field - Polymenakou, Paraskevi N.; Nomikou, Paraskevi; Hannington, Mark; Petersen, Sven; Kilias, Stephanos P.; Anastasiou, Thekla I.; Papadimitriou, Vasiliki; Zaka, Eleutheria; Kristoffersen, Jon Bent; Lampridou, Danai; Wind, Sandra; Heinath, Verena; et al. (Frontiers in Microbiology, 2023)
Active hydrothermal vents of volcanic origin provide a remarkable manifestation of life on Earth under extreme conditions, which may have consequences for our understanding of habitability on other terrestrial bodies as well. We performed for the first time, Illumina sequencing of bacterial and archaeal communities on sub-seafloor samples collected from the Santorini-Kolumbo volcanic field. From a total of 646,671 produced V4 sequences for all samples, a total of 10,496 different Operational Taxonomic Units (OTUs) were identified that were assigned to 40 bacterial and 9 archaeal phyla and 14 candidate divisions. On average, the most abundant phyla in all samples were Chloroflexi (Chloroflexota) (24.62%), followed by Proteobacteria (Pseudomonadota) (11.29%), Firmicutes (Bacillota) (10.73%), Crenarchaeota (Thermoproteota) (8.55%) and Acidobacteria (Acidobacteriota) (8.07%). At the genus level, a total of 286 known genera and candidate genera were mostly dominated by members of Bacillus, Thermoflexus, Desulfatiglans, Pseudoalteromonas and Pseudomonas. Interestingly, in most of the stations, the Chao1 values at the deeper layers were comparable to the surface sediment samples denoting the high diversity in the subsurface of these ecosystems. Heatmap analysis based on the 100 most abundant OTUs, grouped the sampling stations according to their geographical location, placing together the two hottest stations (up to 99oC). This result indicates that this specific area within the active Kolumbo crater create a distinct niche, where microorganisms with adaptation strategies to withstand heat stresses can thrive, such as the endospore-forming Firmicutes.